Desktop Tomography System using Planar ECT Device - Shahrulnizahani Mohammad Din; Nur Adila Mohd Razali; Jaysuman Pusppanathan; Chee Pei Song; Ruzairi Abdul Rahim; Leow Pei Linga (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2017)
Miniaturized planar electrical capacitance tomography (ECT) device is fabricated using microfabrication method to accommodate eight planar electrodes to carry out electrical capacitance measurement using tomography technique. Fluids within the detection chamber are detected by the difference of the permittivity parameters. Stagnant and hydrodynamic multiphase samples such as liquid-gas and liquid-liquid are tested. The eight-electrode planar array is fabricated on the copper plated printed circuit board (PCB) and the chamber is fabricated using polymer poly(dimethyl-siloxane) (PDMS). The images of the multiphase sample are reconstructing using Linear Back Projection algorithm (LBP). Computer interface software is developed to display the images of the fluid online. Experimental results show that the reconstructed images closely resemble with the composition of the multiphase sample within the detection chamber.